Numerical analysis of applied magnetic field dependence in Malmberg-Penning Trap for compact simulator of energy driver in heavy ion fusion. (May 2016) - Sato, T; Park, Y; Soga, Y; Takahashi, K; Sasaki, T; Kikuchi, T; Harada, Nob
Abstract: To simulate a pulse compression process of space charge dominated beams in heavy ion fusion, we have demonstrated a multi-particle numerical simulation as an equivalent beam using the Malmberg-Penning trap device. The results show that both transverse and longitudinal velocities as a function of external magnetic field strength are increasing during the longitudinal compression. The influence of space-charge effect, which is related to the external magnetic field, was observed as the increase of high velocity particles at the weak external magnetic field.